Disparities in spatial access to neurological care in Appalachia: A cross-sectional health services analysisResearch in context - R. Blake Buchalter; Erik G. Gentry; Mary A. Willis; Marisa P. McGinley (Elsevier, 2023)
Summary: Background: Appalachia is rural and socioeconomically deprived with a heavy burden of neurological disorders and poor access to healthcare providers. Rates of neurological disorders are increasing over time without equal increases in providers, indicating that Appalachian disparities are likely to worsen. Spatial access to neurological care has not been robustly explored for U.S. areas, so we aimed to examine disparities in the vulnerable Appalachian region. Methods: Using 2022 CMS Care Compare physician data, we conducted a cross-sectional health services analysis, where we computed spatial accessibility of neurologists for all census tracts in the 13 states with Appalachian counties. We stratified access ratios by state, area deprivation, and rural-urban commuting area (RUCA) codes then utilized Welch two-sample t-tests to compare Appalachian tracts with non-Appalachian tracts. Using stratified results, we identified Appalachian areas where interventions would have the largest impact. Findings: Appalachian tracts (n = 6169) had neurologist spatial access ratios between 25% and 35% lower than non-Appalachian tracts (n = 18,441; p < 0.001). When stratified by rurality and deprivation, three-step floating catchment area spatial access ratios for Appalachian tracts remained significantly lower in the most urban (RUCA = 1 [p < 0.0001) and most rural tracts (RUCA = 9 [p = 0.0093]; RUCA = 10 [p = 0.0227]). We identified 937 Appalachian census tracts where interventions can be targeted. Interpretation: After stratifying by rural status and deprivation, significant disparities in spatial access to neurologists remained for Appalachian areas, indicating both poorer access in Appalachia and that neurologist accessibility cannot be determined solely by remoteness and socioeconomic status. These findings and our identified disparity areas have broad implications for policymaking and intervention targeting in Appalachia. Funding: R.B.B. was supported by NIH Award Number T32CA094186. M.P.M. was supported by NIH-NCATS Award Number KL2TR002547.